Programa de Educación Sexual (Journal of Parents and Teachers, 2014)
The article discusses the inclusion of sexuality within family planning, detailing its objectives and rationale. The authors also emphasise the importance of training in this area, including an educational proposal to increase young people's training in sexuality.
Keywords: Sexual Education; Sexuality; Educational proposal; Educational changes